ETNOMATEMATIKA POLA TARIAN JEJER JARAN DAWUK BANYUWANGI SEBAGAI INSPIRASI PENGEMBANGAN PAKET TES GEOMETRI - Sandhi, Niluh Shindi Aprilia; Trapsilasiwi, Dinawati; Yudianto, Erfan (Kadikma, 2018)
Ethnomatematics is the application of mathematics in cultural life. The purpose of this study was to describe the ethnomatematic activity of the Jejer Jaran Dawuk Banyuwangi dance in Sanggar Jingga Putih Banyuwangi. The product produced in this study is in the form of geometric teaching materials, namely the test problem Package with the topic of Ethnomatematics. This type of research is qualitative with an ethnographic approach. Data collection methods used are observation and interviews. The research subjects were 3 peoples Banyuwangi Culture, dance teacher, and dancer Jejer Jaran Dawuk Banyuwangi. Ethnomatematics is seen when dancers dance a dance to measure, calculate, and design activities. At the time of the process of determining the time to start the dance and the time of change of movement appeared the concept of counting. When determining the distance between dancers, the concept of measuring distance using nonstandard size appears. When performing dance moves and floor patterns, the concept of designing lines, angles, and waking up appears flat. The results of the study are geometry teaching materials in the form of test packages. The test package is intended for junior high school students of class IX. The test package consists of 3 questions level C5 and 1 question level C6. Keywords: Ethnomatematics, Jejer Jaran Dawuk Dance, Geometry